Impact of educational intervention on reduction of menopausal effects - Maharjan, Ratna Kumari (Journal of Patan Academy of Health Sciences, 2015)
Introductions: It is helpful for women to learn what to expect and what options are available in transition to menopause. The objective of this study was to find out the changes in the level of awareness among premenopausal women after educational intervention. Methods: Study was carried out at mothers’ group of Pinchhen Tole Lalitpur district, Kathmandu, Nepal. One hundred and four respondents were selected using non probability convenience purposive sampling technique. Data were collected before and after educational intervention. Results: The findings reveal that the total awareness score was 26.81 in pre-test and 31.97 in post test. The grand mean score of awareness was 24.81 in pre-test and 29.85 in post test. Standard deviation was 3.47 and 0.50 in pre-test and post-test respectively. The overall difference in knowledge between pre-test and post-test was highly significant. Conclusions: Educational intervention among premenopausal women is highly significant in establishing and strengthening awareness about menopausal symptoms and its reduction measures. Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):55-57